Utilization of Technology in Donuts Business - Hutabarat, Nauas Domu Marihot Romauli; Ambarita, Himsar; Sinamo, Karina Nola (Talenta Publisher Universitas Sumatera Utara, 2019)
One of the purpose of community service activities is to help partner to find solutions for the problems on running their businesses. Partner was found lack of knowledge for the basic principles of food safety, which the daily donuts production’s tools are very simple and with conditions that are not safe on food processing, not familiar with online marketing and the lack of utilization of the remaining egg whites from the donuts production. The methods that used in this activity are an approach to partner, designing and making equipment to assist the production process such as proofing cabinet and deep fryer machine, providing knowledge about how importance of hygiene and sanitation of tools in producing food, training of baking egg white-based sponge cake and training of making instagram. With those activities, it expected to grow the understanding and knowledge of partner so they can compete with other businesses running in the same field.